Dietary EVOO Polyphenols and Gut Microbiota Interaction: Are There Any Sex/Gender Influences? - Massimo D'Archivio; Carmela Santangelo; Annalisa Silenzi; Beatrice Scazzocchio; Rosaria Varì; Roberta Masella (MDPI AG, 2022)
Accumulating evidence indicates that regular consumption of extra virgin olive oil (EVOO), the main source of fat in the Mediterranean diet, is associated with beneficial health effects and a reduced risk of developing chronic degenerative disorders. The beneficial effects of EVOO can be attributed to its unique composition in monounsaturated fats and phenolic compounds that provide important antioxidant, anti-inflammatory, and immune-modulating activities. On the other hand, it is well known that the gut microbiota has several important roles in normal human physiology, and its composition can be influenced by a multitude of environmental and lifestyle factors, among which dietary components play a relevant role. In the last few years, the two-way interaction between polyphenols, including those in EVOO, and the gut microbiota, i.e., the modulation of the microbiota by polyphenols and that of polyphenol metabolism and bioavailability by the microbiota, has attracted growing attention, being potentially relevant to explain the final effects of polyphenols, as well as of the microbiota profile. Furthermore, sex and gender can affect dietary habits, polyphenol intake, and nutrient metabolism. Lastly, it has been recently suggested that differences in gut microbiota composition could be involved in the unequal incidence of metabolic diseases observed between women and men, due to sex-dependent effects on shaping gut microbiota profiles according to diet. This review summarizes the most recent studies on the relationship between EVOO polyphenols and the gut microbiota, taking into account possible influences of sex and gender in modulating such an interaction.